ADAPTATION OF E-LEARNING DISRUPTION THROUGH ZOOM IN PANDEMIC COVID19 - RININTHA PARAMES WARI (Jurnal MoZaiK, 2020)
The purpose of this study is to find out how to adapt disruption in learning E-Learning using the zoom application in the pandemic covid19. With the determination of BNPB regarding PSBB and also the Board of Trustees and Kepwal regarding the implementation of PSBB, then the Tangerang City Government limits all activities and hopefully all people can adjust to the current situation. Because E-learning has been announced in the Republic of Indonesia Ministry of Education and Culture Regulation No. 109/2013 Regarding the Implementation of Distance Education in Higher Education, this learning method is already familiar among students especially millennia.From the results of the author's research using qualitative research it can be seen that based on the results of interviews and existing data it can be concluded learning from home (study from home) or when workers work from home (work from home) Zoom application is an application that is often used as learning Media. In the beginning of user learning, there are technical constraints and ignorance of the operation of the application. But with the understanding of the use of periodic and content (content) an interesting learning can make students or audiences interested, especially in the application students can interact with the host or instructor namely teachers, lecturers, instructors and others so that they are comfortable and accustomed to using the application Keywords: Adaptation disruption, E-Learning, Zoom Cloud Meeting